Development of a 83mKr source for the calibration of the CENNS-10 liquid argon detector. (1st April 2021) - Akimov, D.; An, P.; Awe, C.; Barbeau, P.S.; Becker, B.; Belov, V.; Bernardi, I.; Blackston, M.A.; Blokland, L.; Bolozdynya, A.; Cabrera-Palmer, B.; Chen, N.; et al.
Abstract: We report on the preparation of and calibration measurements with a 83 mKr source for the CENNS-10 liquid argon detector. 83 mKr atoms generated in the decay of a 83 Rb source were introduced into the detector via injection into the Ar circulation loop. Scintillation light arising from the 9.4 keV and 32.1 keV conversion electrons in the decay of 83 mKr in the detector volume were then observed. This calibration source allows the characterization of the low-energy response of the CENNS-10 detector and is applicable to other low-energy-threshold detectors. The energy resolution of the detector was measured to be 9% at the total 83 mKr decay energy of 41.5 keV. We performed an analysis to separately calibrate the detector using the two conversion electrons at 9.4 keV and 32.1 keV.